Cold Spray Coatings Morphology - A. Ștefan; D.-L. Chicet; B. Istrate; C. Munteanu (Archives of Metallurgy and Materials)
In the Cold Spraying technology, the coatings are produced as a result of the supersonic acceleration of the particles in a gas jet, at temperatures below the melting/phase transformation point of the sprayed material. In this paper, the morphology of a Ni/CrC cold spray coating is studied, based on the identification of the particle’s characteristic at various magnifications, both on cross-section and on the surface of the samples. The layer appearance is continuous, uniform and sinuous, no adhesion defects were observed at the substrate-coating interface, and the plastic deformation of the steel was highlighted. The elemental chemical analysis on the sample cross-section, together with the distribution map shows that the carbide particles have retained their sphericity to a large extent, being uniformly embedded in the Ni matrix, as a result of the plastic deformation. This allows a higher thickness of the cold spray coatings comparatively to the ones obtained with the other thermal spray methods that imply high temperatures of the gas jet and layered microstructures.